IMPROVING THE STUDENTSâ SPEAKING SKILL THROUGH ROLE PLAY TECHNIQUE TO THE FIRST SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF PGRI UNIVERSITY PALEMBANG - Uzer, Yuspar (Jurnal Dosen Universitas PGRI Palembang)
Abstract : This research entitles âIMPROVING THE STUDENTSâ SPEAKING SKILL THROUGH ROLE PLAY TECHNIQUE TO THE FIRST SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF PGRI UNIVERSITY PALEMBANGâ. The problem of this study was â is it effective improving the studentsâ speaking skill through role play technique to the first semester students of English department of PGRI University Palembang?â. The method that was used in this study was pre-experimental method by type the one group pre-test and post-test design, the population of this study was all the first semester studentsâ of English department of PGRI University Palembang in the academic year of 2013/2014. The total number of populations was 116 students. The sample of this study was class I.B consisted of 38 students in convenient sampling. Based on the data analysis, there was difference between studentsâ average scores of pre-test and post-test. The average scores of pre-test was 55.25 and the average scores of post-test was 70.83. Based on the data analysis the result of matched t-test was 23.60 and the critical value in the t-table was 1.703. It means that t-obtained was higher than t-table, and automatically the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It means that improving the studentsâ speaking skill through role play technique to the first semester students of English department of PGRI University Palembang was effective.Â Keyword : improving, speaking skill, effective